HUBUNGAN POLIMORFISME GEN TLR 9 (RS5743836) DAN TLR 2 (RS3804099 DAN RS3804100) DENGAN PEMBENTUKAN ANTI-HBS PADA ANAK PASCAVAKSINASI HEPATITIS B - Ina Rosalina (Universitas Padjadjaran, 2012)
Current hepatitis B remains a worldwide health problem because it can cause chronic liver disease to hepatocellular carcinoma. One of the most important prevention is to vaccinate infants according to program. However, approximately 5-10% of healthy people fail to produce protective antibodies to the hepatitis B pasca vaccination, mean anti-HBs titers obtained <10 mIU/mL, are vulnerable to viral hepatitis B. One of the contributing factors is the disruption toll like receptor. This study aims to determine the Relation of polymorphisms gene toll like receptor 9 and 2 to the formation of anti-HB s in children pasca vaccination hepatitis B. At the time of blood sampling, the subjects were in good health, birth weight> 2500 g, and had a hepatitis B vaccination according to the program. Crossectional study conducted during the period 2010 to 2012. Obtained consisted of 162 infant boys 82 (50.6%) boys, 80 (49.4%) girls, with an age range 6-13.2 months (median 11.3). Were recorded characteristics, age, vaccination schedule, weight, and physical examination prior to blood sampling. Examination of anti-HBs titers, and examination of TLR 9 by restriction enzymes BstNI and TLR 2 by using the enzyme MwoI and MspI, which previously carried out DNA isolation. Statistical analysis using chi square for genotype and to use statistical tests HAPSTAT haplotype. The results obtained by 15 people (9.4%) anti-HBs titers <10mIU/mL (<2:00 - 8.45mIU/mL as non-response, based on the number of non response is obtained prevalence 9.4% (95% CI: 9.86 to 13, 9%). group with anti-HBs levels <10-100 mIU / mL a number of 144people (90.6%) referred to as a response. Detection of polymorphisms TLR9 -1237 T / C (rs5743836 T / C) with the enzyme BstNi. Found 6 the response of people on the subject. Detection of TLR2 gene polymorphism (rs3804099) with an enzyme found in 20 restrictions MwoI the subject response, whereas with the enzyme MspI restriction on TLR2 gene (rs3804100) obtained 1 (100%) heterozygote mutation in subject responses. Of the three haplotype The visible presence of an effect on the formation of anti-HBs after hepatitis B vaccination.